Projecting Hydrological Responses to Climate Change Using CMIP6 Climate Scenarios for the Upper Huai River Basin, China - Bian, Guodong; Zhang, Jianyun; Chen, Jie; Song, Mingming; He, Ruimin; Liu, Cuishan; Liu, Yanli; Bao, Zhenxin; Lin, Qianguo; Wang, Guoqing (Frontiers in Environmental Science, 2021)
The influence of climate change on regional hydrological cycle has been an international scientific issue that has attracted more attention in recent decades due to its huge effects on drought and flood. It is essential to understand the changing pattern of regional hydrological characteristics in the context of global warming for developing flood mitigation and water utilization strategies in the future. This paper aims to provide a general overview of changes in future runoff and flood for the Upper Huai River basin by combining future climate scenarios, hydrological model and flood frequency analysis. The Daily bias correction (DBC) statistical downscaling method is used to downscale the Global Climate Model (GCM) outputs from the Sixth Phase of the Coupled Model Inter-comparison Project (CMIP6) and generate future daily temperature and precipitation series. The Xinanjiang (XAJ) hydrological model is driven to project changes in future seasonal runoff under SSP245 and SSP585 scenarios for two future periods 2050s (2031–2060) and 2080s (2071-2100) based on model calibration and validation. Finally, the Peaks over Threshold (POT) method and Generalized Pareto distribution (GP) are combined to evaluate the changes of flood frequency for the upper Huai River basin. The results show that: (1) GCM models project that there has an insignificant increasing trend in future precipitation series, while an obvious increasing trend is detected in future temperature series; (2) average monthly runoffs in low-flow season have the decreasing trends under SSP245 and SSP585 scenarios during the 2050s, while there has an obvious increasing trend of average monthly runoff in high-flow season during the 2080s; (3) there is a decreasing trend in design floods below the 50-year return period under two future scenarios during the 2050s, while there has an significant increasing trend in design flood during the 2080s at most cases and the amplitude of increase becomes larger for larger return period. The study suggests that future flood will probably occur more frequently and an urgent need to develop appropriate adaptation measures to increase social resilience to warming climate over the Upper Huai River basin.